Keanekaragaman Insekta yang Terdapat di Hutan Pendidikan dan Pelatihan Universitas Muhammadiyah Bengkulu - Pariyanto Pariyanto; Reny Dwi Riastuti; Mifta Nurzorifah (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2019)
The purpose of this study was to determine the diversity of insects found in the forests of Education and Training at the University of Muhammadiyah Bengkulu in Bengkulu Tengah Regency. The method used in this study is the survey method. Observations were made directly to the study site, and sampling was done by exploring the research location. The study was conducted in December-January 2019. The results of the study, insects found in the Forest of Education and Training University of Muhammadiyah Bengkulu, Central Bengkulu District were obtained 326 individuals consisting of 13 families with 16 species, namely: Pheropsophus verticalis (Tiger beetle), Tenebrio molitor (Beetle caterpillar), Leptocorisa acuta (Walang sangit), Tibicen linnei (Tonggeret), Dolichovespula sylvestris (Tree wasp), Oecophylla smaragdina (Ant-rang), Dolichoderus thoracicus (Black ant), Tanaecia iapis (Tree wasp), Oecophylla smaragdina (Ant-rangung), Dolichoderus thoracicus (Black ant), Tanaecia iapis (Tree wasp) stoli (black spotted butterfly), Valanga nigricornis (wood grasshopper), Acrida conica (green grasshopper), Gryllus bimaculatus (cricket), Scambophyllumson guinolentum (katydid grasshopper), Gryllotapa orientalis (ground dog), Gryllus bimaculatus (cricket), Scambophyllumson guinolentum (katydid grasshopper), Gryllotapa orientalis (earth dog), Gryllus bimaculatus (cricket), Scambophyllumson guinolentum (grasshopper katydid) Phaenopharos khaoyaiensis (grasshopper twigs). From all Insect families found, a Diversity Index of 1.031 was obtained, indicating that diversity was classified as moderate. The results of measurements of ecological factors in the forest are temperatures ranging from 26oC-31oC and humidity 87% -90%. In conclusion, the level of insect diversity in the forests of Education and Training at the University of Muhammadiyah Bengkulu in Bengkulu Tengah Regency is classified as moderate, with the discovery of 13 families and 16 species of insects. Keywords :diversity, forest, insecta.